Flood Routing Simulation and Propagation Law Analysis in Three Gorges Reservoir Area - WANG Jue; ZHANG Hairong; SUN Zhenyu; ZHANG Mingliang (Renmin Zhujiang)
The Saint-Venant equation is discretized by the Preissmann four-point implicit difference scheme and then solved by the three-step solution method of the channel-junction-channel to build a one-dimensional hydrodynamic model of the Three Gorges Reservoir area.The simulated results of the flood routing process in flood seasons in 2020 and 2021 are in good agreement with the measured values.This indicates that the model can accurately calculate the flood routing process in the Three Gorges Reservoir area.In addition,the model is used to explore the flood propagation laws in the reservoir area.The results show that the high flood discharge from the upstream has a great effect on the rise in the water level at the reservoir tail,and the jacking effect of the water level at the dam site spreads to the vicinity of Cuntan Station.Under different flow conditions, it takes about 23~44 h for the flood in the reservoir area to evolve from Zhutuo to the dam site.The flood propagation time is negatively correlated with water level and positively correlated with peak discharge.The analysis of the water level-flow relationship at Cuntan Station shows that the simulated values are in good conformity with the measured ones, and the water level-flow curve of the flooding process at Cuntan Station is in a complex “rope-loop” shape.The results of this study can provide technical support for flood scheduling and forecasting at the stations in the reservoir area.